Manipulation of Sound Properties by Acoustic Metasurface and Metastructure - Zhao, Jiajun; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This thesis focuses on the manipulation of sound properties by artificial materials. It elaborates on the fundamental design of acoustic metasurfaces and metastructures as the extension of metamaterials, and their functionality in the manipulation of sound properties. A broad and comprehensive guideline of designing acoustic metasurfaces and metastructures is also provided. Based on the proposed subwavelength metasurfaces and the metastructures with a simplified layout, multiple potential applications are demonstrated. This thesis will appeal to acoustic engineers and researchers who are interested in designing acoustic artificial structures.
Introduction -- Manipulating Acoustic Wavefront with Metasurface of Inhomogeneous Impedance -- Redirecting Acoustic Waves Out of the Incident Plane -- Manipulating Acoustic Focus with an Active Metasurface Piezoelectric Transducer -- Realizing Acoustic Cloaking and Near-Zero Density with Acoustic Metastructure -- Future Work.
Keywords: Surfaces (Technology).; Thin films; Acoustical engineering; Acoustics; Surfaces, Interfaces and Thin Film; Engineering Acoustics; Acoustics